Time-Canal Surfaces Around Biharmonic Particles and Its Lorentz Transformations in Heisenberg Space-Time - Korpinar, Talat; Turhan, Essin (Springer/Plenum Publishers, 2014)
In this work, we introduce a new space-time using Heisenberg group and call this space as Heisenberg space-time . We give a geometrical description of time-canal surfaces around timelike biharmonic particle in . Moreover, we obtain Lorentz transformations this particles. Additionally, we illustrate our results. Finally, we characterize charged bihamonic particles in electromagnetic fields on Heisenberg space-time.
Keywords: Canal surface; Energy; Bienergy; Heisenberg group; Faraday tensor; Lorentz transformations